2016
DOI: 10.1111/cch.12322
|View full text |Cite
|
Sign up to set email alerts
|

Interagency collaboration in children and young people's mental health: a systematic review of outcomes, facilitating factors and inhibiting factors

Abstract: The results are consistent with findings from previous reviews of interagency collaboration across adult and child services: there were some indications of benefit; and facilitating and inhibiting factors involved working relationships and multi-agency processes, resources and management. The identification of these factors has implications for practitioners, service managers, trainers, commissioners and researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
158
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(184 citation statements)
references
References 48 publications
20
158
0
6
Order By: Relevance
“…Consistent with the extant literature on interprofessional collaboration, which suggests that collaborative care among interagency providers of mental health services is facilitated by mutual valuing, respect, and trust (Bramesfeld et al, 2012; Cooper et al, 2016), these providers indicated that when they had an established relationship or familiarity with a PCP they were more likely to contact them about a shared client and the exchange of information was more efficient. Further, several mental health providers evaluated the success of past communication exchanges based upon the pediatrician’s response to them.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Consistent with the extant literature on interprofessional collaboration, which suggests that collaborative care among interagency providers of mental health services is facilitated by mutual valuing, respect, and trust (Bramesfeld et al, 2012; Cooper et al, 2016), these providers indicated that when they had an established relationship or familiarity with a PCP they were more likely to contact them about a shared client and the exchange of information was more efficient. Further, several mental health providers evaluated the success of past communication exchanges based upon the pediatrician’s response to them.…”
Section: Discussionsupporting
confidence: 59%
“…The challenges of such interprofessional collaboration have been well documented throughout the healthcare arena (Hewett et al, 2009; Lewin & Reeves, 2011; McDougall et al, 2016; Watson et al, 2016), as well as specifically within children’s services (Cooper et al, 2016; Easen et al, 2000; Salmon, 2004). Among many identified structural, individual, and service level barriers, lack of effective communication among providers is consistently cited as a key hindrance to interagency collaboration in children’s mental health services (Cooper et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…leading to a lack of shared information about particular patients [26]. This barrier was especially mentioned in studies on integrated mental healthcare provision [2526]. …”
Section: Resultsmentioning
confidence: 99%
“…Although such barriers are mentioned in various studies of integrated care in inter-organisational settings – partly as the main focus and partly as a by-product while elaborating on other facets of inter-organisational collaboration – so far no systematic review of the relevant literature has been compiled. Various literature reviews focus on inter-organisational collaboration and networks in different industries [222324], but few of these explicitly addresses barriers [122526], often with a very indication-specific focus on healthcare settings. Several empirical works address barriers to the delivery of integrated care in inter-organisational settings, but mostly focus on aspects specific to their case [1127] and lack theoretical embedding.…”
Section: Introductionmentioning
confidence: 99%